Sistem Informasi Manajemen Pph 21 Pada Pt Mesindo Tekninesia - Nina Meliana; Khoiratun Nadhiroh; Agus Sugiharto (Fakultas Ilmu Komputer dan Desain - Unsurya, 2023)
Management Information System or commonly called SIM is needed by an organization or company in its internal control. In the current era of digital transformation, it is very necessary to develop a driver's license in companies, one of which is the PPh21 tax application.Seeing the conditions above, the author intends to conduct research aimed at providing solutions through the study of various theories and observations in the field in the context of developing the PPh 21 tax application. Building a SIM uses PHP as the program and phpMyAdmin as the database. The application development methodology used is the Waterfall methodology, consisting of phasing requirements, design, implementation, integration and testing, and operation and maintance. The results of this study can simplify the PPh 21 tax calculation system and minimize the difficulty of processing tax data so that the PPh 21 tax system becomes neat, orderly, and more efficient.